Resistance training for metabolic dysfunction-associated steatotic liver disease:a systematic review and meta-analysis - Chen, Yun; Qiao, Xiaoya; Zou, Xinyi; Xu, Kai; Gu, Zhongke; Chen, Gangrui; Dai, Jiansong (Frontiers in Physiology, 2026)
ObjectiveThe aim is to systematically assess the impact of resistance exercise on patients diagnosed with metabolic dysfunction-associated steatotic liver disease (MASLD).MethodsRandomized controlled trials (RCTs) focusing on resistance exercise for MASLD/NAFLD were sourced from PubMed, Embase, the Cochrane Library, Web of Science, Scopus, and CNKI databases, (covering all entries from inception to 18 March 2025. The Cochrane Risk of Bias Tool was utilized for quality evaluation, and RevMan 5.3 software was used for conducting the meta-analysis.ResultsEleven RCTs, involving 395 participants, were included in the analysis. The meta-analysis revealed that alanine aminotransferase (ALT) levels were significantly decreased (MD = −4.44 U/L, 95% CI = −8.84 to −0.03, Z = 1.98, P = 0.05). No significant difference was observed in aspartate aminotransferase (AST) levels (MD = −0.18 U/L, 95% CI = −6.70 to 6.34, Z = 0.05, P = 0.96). Among the eight imaging assessment studies, seven reported substantial reductions in liver fat content, whereas one study indicated no effect. No significant difference in clinical compliance was detected between the groups (RR = 0.99, 95% CI = 0.89 to 1.10, P = 0.92), and no serious adverse events were documented.ConclusionResistance exercise notably enhances ALT levels and hepatic steatosis in patients with MASLD. The recommended minimum effective dosage is whole-body multi-muscle training, consisting of 8–10 exercises at 60%–80% of one-repetition maximum (1RM) intensity, performed at least three times weekly for a minimum of 12 weeks. This intervention is particularly advantageous for patients with elevated ALT levels who are unable to tolerate aerobic exercise, and it appears to be safe. Nonetheless, further research involving larger sample sizes is required to confirm its long-term efficacy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251050504, identifier CRD420251050504.